Beyond monoamines: II. Novel applications for PET imaging in psychiatric disorders. Issue 3 (29th July 2022) - Royse, Sarah K.; Lopresti, Brian J.; Mathis, Chester A.; Tollefson, Savannah; Narendran, Rajesh
Abstract: Early applications of positron emission tomography (PET) in psychiatry sought to identify derangements of cerebral blood flow and metabolism. The need for more specific neurochemical imaging probes was soon evident, and these probes initially targeted the sites of action of neuroleptic (dopamine D2 receptors) and psychoactive (serotonin receptors) drugs. For nearly 30 years, the centrality of monoamine dysfunction in psychiatric disorders drove the development of an armamentarium of monoaminergic PET radiopharmaceuticals and imaging methodologies. However, continued investments in monoamine‐enhancing drug development realized only modest gains in efficacy and tolerability. As patent protection for many widely prescribed and profitable psychiatric drugs lapsed, drug development pipelines shifted away from monoamines in search of novel targets with the promises of improved efficacy, or abandoned altogether. Over this period, PET radiopharmaceutical development activities closely parallelled drug development priorities, resulting in the development of new PET imaging agents for non‐monoamine targets. In part two of this review, we survey clinical research studies using the novel targets and radiotracers described in part one across major psychiatric application areas such as substance use disorders, anxiety disorders, eating disorders, personality disorders, mood disorders, and schizophrenia. Important limitations of the studies described are discussed, as well as key methodologic issues, challenges to the field, and the status of clinical trials seeking to exploit these targets for novel therapeutics. Abstract : The emergence of positron emission tomography in the late 1970s facilitated non‐invasive assessments of brain function. In concert with conventional treatment approaches in psychiatry, positron emission tomography (PET) radiotracer development activities have historically emphasized monoaminergic targets, such as serotonin and dopamine receptors and transporters. More recently, psychiatric drug development priorities have shifted away from monoamines in search of novel targets offering improved efficacy and tolerability. This two‐part review surveys PET radiotracer developments paralleling major central nervous system (CNS) targets under investigation as novel treatment approaches for psychiatric disorders and applications thereof. Depicted are the primary cellular sources of these novel targets in the human brain.